KLASTER INDUSTRI KECIL DAN KERAJINAN RUMAH TANGGA DI JAWA BARAT - Yanuarita Hendrani; Hamfri Djajadikerta; Urip Santoso (Research Report - Humanities and Social Science, 2009)
The success of Silicon Valley as a technological industrial cluster in the US has made industrial cluster gain a popularity among local authorities in developing countries as a means of enhancing local competitiveness. In West Java, most industrial clusters grow naturally with minimal assistance from the government. They grow naturally as some families’ inherited skills are transfered to or imitated by their neighbors and other family members in the same village.The purpose of this research is to identify the clusters and their sizes in West Java. Using 2 sources data from BPS, namely, the 2006 census of formal small scale industries and the 2005 survey of informal small scale and home industries, it is found that the largest clusters in term of size are found in Bogor municipal, bandung municipal, Cirebon municipal, Tasikmalaya city and municipal and Bekasi municipal. The product varies from palm suga, rattan furniture, brick and roof tiles, embroidery and garment. It is also found that industrial clusters in West Java are more of Sonobe’s and Otsuka’s concept of “one village one product” with few related businesses located in the same location.Keywords: industrial cluster, labor market pooling, specialized suppliers, knowledge spillover, small scale industry, home industry